Procedures Used in Translating Cultural Words of the Movie Eat Pray Love - Henny Halim; Rahmanti Asmarani (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2019)
Translation is a kind of activity of transferring the authorâ€™s idea from source language into target text, the culture involving. Some cultural words are often considered as the difficulties to transfer. â€œEat Pray Loveâ€ is an American biographical romantic which has received many positive reviews and later in 2009, it became the New York Times Best Â Seller for 187 weeks. This research is conducted to find the pattern of cultural words translation procedures used by the translator in translating the transcript and subtitle. The unit of analysis of this research was in the form of words, phrases and clauses in the movie entitled Eat Pray Love. This study has the aim to gain a complete understanding in translating cultural words, the problems that may occur then how to solve it. The descriptive-qualitative approach has been applied during this research then selecting the cultural words. The result of this study reveals that from 126 cultural words found in the movie. The frequency of cultural words found the most are material culture and social organization. The process of rendering the selected cultural words in Eat Pray Love movie into target language mostly used borrowing procedure